«Руки в тісті» - інноваційний освітінй проект у Франці - Лавриченко, Наталя (Studies in Comparative Education, 2015)
Статтю присвячено інноваційному освітньому проекту, реалізованому у Франції, під назвою «Руки в тісті». З’ясовано зміст поняття «Руки в тісті». Охарактеризовано основні особливості, принципи та переваги проекту, а також труднощі, які виникають в процесі його запровадження. Зроблено висновок про значення проекту для модернізації французької освіти і можливості й адаптації цього досвіду в умовах інших освітніх систем. Статья посвящена инновационному образовательному проекту под названием «Руки в тесте». Выяснено содержание понятия «Руки в тесте». Описано основные особенности, принципы и преимущества проекта, а также трудности, которые могут возникнуть в процессе его внедрения. Сделано вывод о значение проекта для модернизации французской системы образования и возможности заимствования и адаптации в условиях других образовательных систем. The article is devoted to the innovative education project «Hands in dough» realized in France. It has been justified that the education system of France needed some innovational approaches. The content of the notion «Hands in dough» has been clarified and the place of origin and the creator of this idea have been mentioned. The history of realizing the project has been given. The so called «year of sensitization» has also been mentioned in the context as an important stage in establishment of the innovative project. According to the author, the new project met irony and distrust from ordinary people and scientists as well, so ten basic principles of the project have been described in order to justify its effectiveness. The author also describes another problem having emerged while putting «Hands in dough» into action: the lack of teachers with necessary qualification. It caused creation of the three-year plan for resource and staff supply as solution. The main peculiarities of the «Hands in dough» methodology have been given and characterized. One of them is the experimental character of studying when students ask questions, and teachers are not supposed to answer, but to help children find the right answer by themselves. To justify it and illustrate what actually the process is like, several examples of lessons have been given. Another specific feature of a typical lesson given according to the project «Hands in dough» described in the article is keeping personal diaries by students. It has been emphasized that giving «Hands in dough» lessons demands that a teacher should have special psychological and pedagogical preparation taking into account all the information given in the article. Some other demands to pedagogues using «Hands in dough» project have been enumerated. The author draws a conclusion about importance of the project for French education system modernization and about the possibility of its borrowing and adjusting to other education systems. But the necessity of providing all the required conditions has been accentuated.